Podmiotowość prawnomiędzynarodowa Wspólnot Europejskich oraz Unii Europejskiej - Rewizorski, Marek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
One of the main issues in the debate on the Treaty of Lisbon was to determine the legal international status of the European Union. The doctrine of international public law and European law stipulates personality as the ability to acquire rights and enter into international commitments. Before the Treaty of Lisbon came into force a highly animated and varied discussion continued on this issue. Among other things, it concerned the issues of whether international organizations are the subjects of international law, the nature of their subjectivity (primary or secondary), the relationship between the Community’s founding treaties, and, finally, whether European law constitutes an autonomous legal system. The most serious controversies, however, were raised by the legal international qualification of the European Union. In the opinion of a portion of representatives of European law, the EU was considered to be an international organization although it did not have legal personality, in contrast to the European Community. Therefore, it was usually defined as a specific structure in statu nascendi. This dispute was ultimately concluded by the Lisbon Treaty which replaced the three-pillar legal structure with a uniform international organization, and the European Community ceased to function. Yet the new legal system retained the European Atomic Energy Community, which seems an inconsistent and flawed decision, albeit a politically justified solution.